Textual Transcoders Quranic Duration from 711m to 1492m - Talib Mahdi, Ali; Atiyah Hameedi, Majid; Jasim Abdullh Gharbawee, Hakim (International Journal of Psychosocial Rehabilitation, 2020)
It is no secret to anyone that the Noble Qur’an came from God Almighty, a miracle in everything, organized, prose, literature, eloquence and fluency. The pundit of the language failed its pillows and it was and still will have a clear impact on literature in general, including Andalusia in particular that literature whose effects are still thunderous in our Arab heritage until now has given birth to many great writers and organizers and poets who are famous. Writer The study dealt with the effect of the Qur’an, intertextuality and aspiration, frankness at various levels and denominations, including quotation and its implications for the writers of literary prose in Andalusia during that period, citing some of those prose proofs in an artistic and literary style that is easy to read to the reader.